2023
DOI: 10.1007/s13201-023-01970-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Saccharomyces cerevisiae as new technique to remove polystyrene from aqueous medium: modeling, optimization, and performance

Abstract: MPs are widely found in various environments. PS is the second most common microplastic in sediments, freshwater, soil, and coastal ecosystems. S. cerevisiae was studied as a biocoagulant due to its advantages such as ease of use, non-toxicity, large-scale cultivability and low cost. The aim of this study was to evaluate the efficiency of S. cerevisiae in removing PS from aqueous solutions. BBD was used to determine the optimal removal conditions. The MPs were washed, dried, crushed, sieved, and kept in a clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In some studies such as oak powder 19 , Aspergillus sp. 28 , and S. cerevisiae 29 was used to remove MPs from aquatic environment. S. platensis is a type of blue-green microalgae that is utilized for the purpose of eliminating pollutants, including heavy metals, organic compounds, and other contaminants, from aquatic environments 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In some studies such as oak powder 19 , Aspergillus sp. 28 , and S. cerevisiae 29 was used to remove MPs from aquatic environment. S. platensis is a type of blue-green microalgae that is utilized for the purpose of eliminating pollutants, including heavy metals, organic compounds, and other contaminants, from aquatic environments 30 .…”
Section: Introductionmentioning
confidence: 99%
“…MPs are synthetic polymer particles or fibers with sizes ranging from 0.1 to 5000 μm, and their concentration in water bodies and shorelines can be quite high (Nasrabadi et al 2023). Each year, approximately 300 million tons of MPs enter the environment, mostly in soil and freshwater environments (Zhang et al 2021;Zahmatkesh Anbarani et al 2024). MPs have a small size, large surface area, and high hydrophobicity, making them ideal carriers for various pollutants like pesticides, PCBs, cyanide, PAHs, Antibiotics, and heavy metals, which can easily spread throughout the ecosystem (Bonyadi et al 2012;Esmaili et al 2023;Yu et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated the effectiveness of aquatic plants (algae) and certain fungi in the removal of microplastics. Zahmatkesh Anbarani et al [ 38 ] found that Saccharomyces cerevisiae achieved 98.81 % polystyrene microplastic removal under optimized conditions, revealing its potential as a natural, eco-friendly biocoagulant. Similarly, Nasrabadi et al [ 39 ] reported that a significant portion of studies (34.21 %) in their review has found polymer biodegradation over 21–30 days, with 44 % focusing on low-density polyethylene (LDPE) biodegradation by various Aspergillus species.…”
Section: Introductionmentioning
confidence: 99%